2016
DOI: 10.1038/srep32481
|View full text |Cite
|
Sign up to set email alerts
|

On the saliva proteome of the Eastern European house mouse (Mus musculus musculus) focusing on sexual signalling and immunity

Abstract: Chemical communication is mediated by sex-biased signals abundantly present in the urine, saliva and tears. Because most studies concentrated on the urinary signals, we aimed to determine the saliva proteome in wild Mus musculus musculus, to extend the knowledge on potential roles of saliva in chemical communication. We performed the gel-free quantitative LC-MS/MS analyses of saliva and identified 633 proteins with 134 (21%) of them being sexually dimorphic. They include proteins that protect and transport vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 71 publications
8
80
0
Order By: Relevance
“…Interestingly, those lipocalins that are produced by lacrimal and nasal tissues, are finally transported to the oral cavity where they are detectable in saliva (Stopka et al, 2016). These proteins are also spread onto the fur with saliva during selfgrooming where they may function as chemical signals.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, those lipocalins that are produced by lacrimal and nasal tissues, are finally transported to the oral cavity where they are detectable in saliva (Stopka et al, 2016). These proteins are also spread onto the fur with saliva during selfgrooming where they may function as chemical signals.…”
Section: Introductionmentioning
confidence: 99%
“…Lacrimal expression of Mup4 and the presence of MUP4 with its ligands in the mouse tears (i.e. along with other signals) and saliva (Stopka et al 2016) may explain the observation of Luo et al (Luo et al 2003;Luo & Katz 2004), who reported that mouth and facial areas are the first and the most frequently investigated areas during mouse social contacts. Moreover, these areas are investigated longer and more frequently in comparison with investigation of the anogenital region.…”
mentioning
confidence: 88%
“…The signals that are transported by MUPs or MUPs themselves have been shown to regulate reproductive behaviour of the receiver (Janotova & Stopka 2011;Ma et al 1999;Novotny et al 1986;Roberts et al 2010;Stopka et al 2007), MUPs have a predictive value for the onset of aggressive behaviour and dispersal tendency in male wild house mice (Rusu et al 2008), and one particular MUP -MUP20 or 'Darcin', which in M. m. domesticus is prevailingly expressed by males, has been reported to predict the outcome of malemale territorial competition (Nelson et al 2015), stimulates inherent female attraction for particular males (Roberts et al 2010), and its level decreases in immune-challenged male mice (Lopes & Konig 2016) which presumably shows that the production of MUP20 / MUPs is costly. In M. m. musculus, however, MUP20 was also detected in the saliva of males and females (Stopka et al 2016). Moreover, MUPs and other lipocalins (e.g.…”
mentioning
confidence: 96%
See 2 more Smart Citations